Examining the Relationship between Transformational Leadership and Organizational Change Effectiveness: A Case Study of Multinational Companies in Baluchistan - Sami, Iqra; Syed, Sumaiya; Afreen, Aleeza (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the impact of transformational management on organizational alternate effectiveness within multinational groups working in Baluchistan, Pakistan. Recognizing the dynamic and hastily evolving commercial enterprise surroundings, this research emphasizes the important role of leadership in navigating via organizational alterations. The look is grounded inside the theoretical framework of transformational management and is posited to influence organizational change tactics seriously, fostering innovation, motivation, and collective imagination and prescience among employees. Through a quantitative study’s methodology, facts were accrued from mid-level managers at Mondelez International, Hub, and Cnergyico Pakistan Limited, Hub, using the Multifactor Leadership Questionnaire (MLQ) and Project Implementation Profile (PIP) survey contraptions. The findings reveal a wonderful correlation between transformational leadership and organizational trade effectiveness, highlighting the importance of transformational leadership behavior, including intellectual stimulation, inspirational motivation, and individualized consideration, in enhancing the success of alternate projects. This takes a look at contributing to the existing body of knowledge by presenting empirical proof of the effectiveness of transformational management in managing organizational change inside the unique socio-economic and cultural context of Baluchistan. The implications of this study are massive for multinational agencies in search of powerful exchange management techniques in diverse and tough environments in force.